Discrimination of grated cheeses by Fourier transform infrared spectroscopy coupled with chemometric techniques - Gori, Alessandro (2012)
Attenuated total re fl ectance Fourier transform infrared spectroscopy (ATR-FT IR), combined with chemometric analysis, was used to classify grated Parmigiano-Reggiano cheese from other grana-type cheeses (so called for their granular texture) from Italy, central and northern Europe. A total of 36 grated cheese samples (21 Parmigian o-Reggiano and 15 Italian and non-Italian non-Protected Designation of Origi n) were analysed. Samples were scanned in the range of 4000-700 1/cm. Two attenuated total reflectance accessories were utilised. Linear discriminant analysis (LDA) and principal component analysis were used to analyse spectral data after applying a moving windows algorithm for wavelength select ion. Both meth ods succe ssfully classi fi ed the four classe s of grated cheese samples, and LDA was found to be the best chemometric approach. ATR-FTIR spectroscopy coupled with LDA is a promising technique, and merits further investigation as a reliable and rapid classification tool that does not require chemical analyses for discrimination of cheese.